The Effects of Exercise on Pain and Reproductive Performance in Female Pregnant Mice With Neuropathic Pain. Issue 5 (October 2019) - Parent-Vachon, Madeleine; Beaudry, Francis; Carrier, Denise; Di Cristo, Graziella; Vachon, Pascal
Pain can have negative, physiological and psychological impacts on pregnancy. Pregnant women are fearful of using pain medication because of teratogenic effects. In this study, we evaluated whether exercise could lower pain sensitivity in pregnant mice with neuropathic pain and reduce the negative effects of maternal pain on newborns. We randomly assigned 32 female mice to one of four groups (eight mice/group): Sham surgery with standard environment (SE) or enriched environment (EE) or spare nerve injury (SNI) with SE or EE. Mice in EE groups had access to an exercise wheel. Mothers were evaluated for mechanical sensitivity with Von Frey filaments and for exercise performance with computerized running wheels. Mice were impregnated 2 weeks after the initiation of EE. Pups were weighed and measured for length at birth and evaluated for negative geotaxis, righting, forelimb grasping, rooting, and crawling at 3 days postpartum and for crawling at 6 days postpartum. Following euthanasia, mothers' frontal cortexes were analyzed for selected neuropeptides. After exercise exposure, only SNI-SE females remained neuropathic. Exercise levels were similar between EE groups. Some brain neuropeptides (endorphins, enkephalins, and oxytocin) from SNI females showed significant differences with exercise. Number of pups was significantly smaller in the SNI-SE group. Significantly more pups died at birth in the SNI-SE group, but pup behavior tests (except righting) were similar across groups. Exercise can reduce neuropathic pain in pregnant mice. Neuropathic pain does not impact motor neurodevelopment of mice pups but does appear to affect litter size and neonatal mortality.